A imagem como manifesto: fragmentos de uma gráfica ativista brasileira - Faca, Camila Carvalho (2022)
In September 2018, millions of Brazilians took to the streets with their posters for the #elenão movement. In this period, there was an intense mobilization by graphic artists, illustrators, scriptwriters, communicators from all over Brazil, who worked creatively and collectively, giving rise to a movement of graphic agitation that started in cyberspace and moved to the streets. This research presents discussions about the production and reproduction of visual protest artifacts, tied to the use of digital networks, specifically addressing the relationships of this visual material with Brazilian society in the context of the 2018 #elenão protests.